Progress in large-scale plasma-focus experiments - Sadowski, M.; Scholz, M. (Вопросы атомной науки и техники, 2005)
This invited talk presents the most important results of theoretical and experimental studies of high-current Plasma-Focus (PF) discharges, as performed recently in a frame of the scientific collaboration of IPJ and IPPLM, Poland. Progress in studies of the breakdown and axial acceleration phase was achieved. Numerical computations showed that a modified MHD model is satisfactory until the maximum compression. In experimental studies the use was made of different diagnostic techniques. Correlations of X-ray pulses with other PF phenomena were analyzed, and differences in polarization of X-ray spectral lines were explained. Fast electronbeams (emitted through the axial channel) were analyzed, and energetic ions (emitted in the forward direction) were measured. Anisotropy of fusion neutrons was investigated and its temporal changes were analyzed. For the first time an optical spectrometer with a high temporal resolution was applied to study the evolution of spectral lines. The main issues of PF studies were also considered. У роботі представлені найбільш важливі результати теоретичних і експериментальних досліджень розрядів у плазмовому фокусі (ПФ), проведених останнім часом у рамках співробітництва між IPJ і IPPLM (Польща). Досягнуто прогрес у вивченні пробою і фази прискорення. Чисельні дослідження показують, що модифікована модель МГД є задовільною до моменту максимальної компресії. В експериментальних дослідженнях було використано різне діагностичне устаткування. Була досліджена кореляція рентгенівського випромінювання з іншими ефектами у ПФ, а також відзначено розходження в поляризації рентгенівських спектральних ліній. Досліджувалися потоки швидких електронів (випроменених через аксіальний канал), і виміряні потоки енергетичних іонів (випроменених у зворотному напрямку). Була досліджена анізотропія термоядерних нейтронів і проаналізовані їхні часовізміни. Уперше для вивчення еволюції спектральних ліній був використаний оптичний спектрометр із високим часовим дозволом. Розглянуті також основні проблеми вивчення ПФ. В работе представлены наиболее важные результаты теоретических и экспериментальных исследований разрядов в плазменном фокусе (ПФ), проводимых в последнее время в рамках сотрудничества между IPJ и IPPLM (Польша). Достигнут прогресс в изучении пробоя и фазы ускорения. Численные исследования показывают, что модифицированная модель МГД является удовлетворительной до момента максимальной компрессии. В экспериментальных исследованиях было использовано различное диагностическое оборудование. Была исследована корреляция рентгеновского излучения с другими эффектами в ПФ, а также отмечено различие в поляризации рентгеновских спектральных линий. Исследовались потоки быстрых электронов (излученных через аксиальный канал), и измерены потоки энергетических ионов (излученных в обратном направлении). Была исследована анизотропия термоядерных нейтронов и проанализированы их временные изменения. Впервые для изучения эволюции спектральных линий был использован оптический спектрометр с высоким временным разрешением. Рассмотрены также основные проблемы изучения ПФ.